Root coverage by coronally advanced flap with connective tissue graft and/or enamel matrix derivative: a meta‐analysis. (12th July 2014) - Cheng, G.‐L.; Fu, E.; Tu, Y.‐K.; Shen, E.‐C.; Chiu, H.‐C.; Huang, R.‐Y.; Yuh, D.‐Y.; Chiang, C.‐Y.
Abstract : Background and Objective: Previous systematic reviews have reported that the use of a coronally advanced flap (CAF) combined with a connective tissue graft (CTG) or enamel matrix derivative (EMD) is more likely to achieve complete root coverage (CRC) than other modalities. However, the details of periodontal parameters and comparisons among a variety of combinations of CAF with CTG and/or EMD are left to be investigated. This study aimed to analyze the differences in periodontal parameters between these treatment modalities. Material and Methods: A literature search was performed using the Cochrane library and MEDLINE (PubMed) for studies focused on the treatment of gingival recession (Miller Class I, II and III) with CAF alone or combined with CTG, EMD or both up to December 2011. Randomized controlled clinical trials with a follow‐up duration ≥ 6 mo were included. The outcome analysis included changes in periodontal probing depth (PPD), clinical attachment level, recession depth (RED) and keratinized tissue width (KTW). Results: Thirteen randomized controlled clinical trials, including 529 Miller Class I–III defects from 321 patients were included. For an increase in KTW, CAF + CTG significantly improved more than CAF alone. CAF + EMD also gained more KTW than CAF alone. EMD reduced PPD, however, a significant difference was not found. Furthermore, the effects on changes of RED and clinical attachment level were not identified in the study. Conclusion: When combined with CAF, CTG contributed more in the increase of KTW, while EMD seemed helpful for wound healing by its potential in PPD reduction. However, further research is needed to clarify the effects on changes in RED and clinical attachment level.